Avaliação ultrassonográfica do bulbo ocular em cães submetidos à facoemulsificação com ou sem implante de lente intraocular - Pavan, P. t. [UNESP]; Ranzani, José Joaquim Titton [UNESP]; Almeida, M. f. [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Brandão, Claudia Valeria Seullner [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2014)
This study aimed to describe and compare the ultrasonographic alterations in dogs' eyes submitted to facectomy with or without intraocular lens implant (IOL), to assist in the diagnosis of possible alterations related to the surgical procedure and IOL implantation. Nineteen dogs with cataract (21 eyes) were submitted to phacoemulsification and late postoperative evaluation (at five years). The animals were initially submitted to complete ophthalmological exams which preceded the sonogram. Dogs were divided in three groups: (CA) aphakic dogs (n= 11); (PP) pseudophakic dogs with implantation of two IOLs in piggyback (n=5) and (PL) pseudophakic dogs with implantation of a veterinary IOL (n = 5). The ultrasound was carried under the administration of a topic local anesthetic, with a multi frequency linear transducer of 10 MHz. Biometric eye measurements were also performed. The clinical alterations observed were IOL dislocation, retinal detachment, asteroid hyalosis, and vitreous degeneration. Ultrasound examination was an excellent diagnostic tool, as it was possible to confirm and classify these changes. The piggyback implant reduced the measurements between the ciliary body and the vitreous chamber obtained from the ocular biometry when compared to other usual procedures, with no difference between the axial length and the anterior chamber.

Este trabalho objetivou descrever e comparar as alterações ultrassonográficas encontradas em bulbos oculares de cães submetidos à facoemulsificação, com ou sem implante de lente intraocular (LIO), no intuito de auxiliar no diagnóstico de alterações decorrentes da cirurgia e do implante da LIO, bem como sua correspondência com alterações clínicas. Dezenove cães portadores de catarata (21 olhos) foram submetidos ao procedimento de facoemulsificação e avaliados no pós-operatório tardio, aos cinco anos de evolução. Constituíram-se três grupos experimentais: afácicos (CA), formados por 11 cães; pseudofácicos (PP), com implante de duas LIOs em piggyback (n=5); e pseudofácicos (PL), com implante de uma LIO veterinária (n=5). Após exame oftálmico, todos foram submetidos ao exame ultrassonográfico, sob anestesia tópica, com transdutor linear multifrequencial de 10MHz; adicionalmente foram avaliadas medidas biométricas dos bulbos do olho. As principais alterações observadas foram: luxação da LIO, descolamento de retina, hialose asteroide e degeneração vítrea. O exame ultrassonográfico mostrou-se como excelente ferramenta diagnóstica e possibilitou a confirmação e a classificação dessas alterações. Na biometria ocular, pelas medidas entre o corpo ciliar e a câmara vítrea, o implante em piggyback resultou em redução destas em relação aos demais procedimentos instituídos, não havendo diferença ente o comprimento axial e a câmara anterior.
Ocular bulb ultrasonographic evaluation in dogs submitted to facectomy by facoemulsification with or without intraocular lens implants
Keywords: cão; biometria ocular; olho; LIO; dog; ocular biometry; eye; IOL